Predicting Electricity Consumption in Misan Province of Iraq Using Univariate Time Series Analysis - AL-Farttoosi, Sami A. S.; Mansouri, Behzad (Opción, 2019)
The goal of this research is to develop a suitable model for forecasting monthly electricity demand in Misan Iraq. Regarding the issue of electricity shortages and post-war industries rebuilding, this information is vital for Iraqi officials. Due to the lack of information on other variables those affecting power con- sumption, the focus of this research is on univariate models for short-term forecasting (up to two years). The data for this study are from January 2009 to June 2019. Several models were fitted to the data in three classes including exponential smoothing methods, Box-Jenkins models and state- space mod- els. Different criteria were used to select the appropriate model. The random- ness of the model residuals was investigated using Liang-Box criterion and the Akaike information benchmarks were calculated for each model. Also, a 12-month period was excluded from the latest data as the hold-out sample and used to test and validate the models predictions. The results show that Box-Jenkins modeling provides better results for these data. Finally, electric- ity consumption forecasts for a 24-month period in Iraq’s Misan province are presented.